QUALITY OF CORPORATE GOVERNANCE - CONTRIBUTION TO IMPROVING COMPANIES PERFORMANCE IN BOSNIA AND HERZEGOVINA - Marin, Slobodan; Tešić, Rade; Šušić, Milan (Journal of process management and new technologies, 2021)
A quality corporate governance system is a basic prerequisite for a sustainable growth economy, more easily increasing the efficiency of the economic system and guaranteeing access to external sources of capital. The level of quality of corporate governance can be defined as the degree of fulfillment of set standards of corporate governance defined at the international and national institutional level. In the new, modern business conditions, with strong dynamic changes in the social and business environment, modern corporate companies, ie their management bodies, are taking on new characteristics, adapting to new requirements and challenges. In this sense, the new demanding business conditions require continuous improvement of corporate governance potential. Based on previous theoretical and empirical knowledge, Bosnia and Herzegovina has the characteristics of a closed corporate governance system in both entities, so, as a basis for developing models for measuring the level of corporate governance, selected models that measure corporate governance in countries with typical closed corporate governance systems. A significant number of studies show that corporations that achieve higher standards and better corporate governance practices also have better business performance results and thus greater value in the capital market. This means that corporations with a higher level of corporate governance also have better financial operating results, easier access to financial capital, and greater value in the capital market. The main purpose of the research is to determine the level of influence of the quality of corporate governance on business performance, ie to determine whether corporations that had good corporate governance had higher business liquidity and vice versa. The main goal of the research is to establish the link and relationship between quality and corporate performance management indicators of the corporation's business.